Development of Disaster Mitigation Learning Structures - I Wayan Gunada; Syahrial Ayub; Aris Doyan; Muhammad Taufik; Kosim Kosim (Jurnal Penelitian Pendidikan IPA, 2020)
Abstract. This research aims to determine the structure of disaster mitigation learning in elementary schools. It is Research and Development also known as RnD study. This research gives a real-life example of how a teacher can teach and embed the awareness about natural disasters in an uncomplicated and fun way, by using the disaster mitigation model of teaching. The study results in one design of a disaster mitigation model of teaching and a teaching structure implementing a scientific approach on disaster mitigation. This research is based on the development and real-life experience of the researcher team in teaching and doing observation and research on the headmaster, teachers, and the students of Mataram 6 elementary school. It is the pilot project of this research, which in return will be implemented in other schools in the urban, coastal area, as well as the mountainous area in Lombok Island. The result shows that the headmaster and the teachers’ response towards the disaster mitigation model of teaching had been really positive, with only 5% of the teachers claims that they are interested, whilst the other 95% claim that the study is extremely interesting for them. The students were very enthusiastic and active during the learning process. Besides, the claim to have meaningful benefit from this mitigation learning. This thus indicated that this mitigation model of teaching and learning can be used as a guide or reference in embedding the awareness for natural disasters among the school community.